FAKTOR-FAKTOR YANG MEMPENGARUHI FOREIGN DIRECT INVESTMENT (FDI) DI KAWASAN ASIA TENGGARA - Cep Jandi Anwar (MediaTrend, 2016)
The need for investment as factors triggering the development of a country has a very important role. Foreign direct investment can be one of the important sources of capital in developing countries, and contribute, the national development by transfer of asset, management, and technology to stimulate the economy of the country. The purpose of this research is to determine the effects of interest rate, inflation, economic growth, openness on foreign direct investment (cases study in 5 South-east Asia countries namely, Indonesia, Malaysia, Thailand, Philippines, and Vietnam period of 2005 to 2012). The analytical method in this study is linear regression analytical method of panel data with Fixed Effect Model (FEM) method to calculate the data is used by Eviews 8 software. The result of this research showed that during 2005 to 2012 the economic growth has positive and significant effect on foreign direct investment. Interest rate, inflation, and openness have negative and significant on foreign direct investment. Simultaneously, independent variable is significantly affect on dependent variable.